Short‐term effects and adverse events of endoscopically applied radiofrequency ablation appear to be comparable with photodynamic therapy in hilar cholangiocarcinoma. Issue 4 (1st August 2016) - Schmidt, A; Bloechinger, M; Weber, A; Siveke, J; von Delius, S; Prinz, C; Schmitt, W; Schmid, RM; Neu, B
Abstract : Background and study aims: Radiofrequency ablation (RFA) is a new endoscopic palliation therapy for malignant biliary obstruction. The aim of this study was to compare the short‐term effects of biliary drainage and adverse events of this technique with the standard of endoscopical treatment of hilar cholangiocarcinoma, photodynamic therapy (PDT). Patients and methods: We retrospectively and since December 2012 prospectively investigated the efficacy and adverse events of RFA in patients with hilar cholangiocarcinoma in two tertiary referral centers between November 2011 and January 2013. The approach of the study was prospective, but because of the large amount of retrospectively included patients, the design of the study is overall retrospective. A group of 20 patients treated with PDT between April 2005 and May 2011 served as a historical control. Results: Fourteen patients received 31 biliary RFAs and 20 patients received 36 PDTs. Within the RFA group, a significant decrease ( p  = 0.046) of the bilirubin level was seen 14 days after the first RFA (3.3 ± 3.9 (mg/dl) versus 2.3 ± 2.6 (mg/dl)). In the PDT group no significant decrease ( p  = 0.67) of the bilirubin level was obtained (4.1 ± 6.9 (mg/dl) versus 3.5 ± 5.3 (mg/dl)). In the PDT group (13/20, 65%) a significantly higher number of premature stent replacements (<3 months) after the first intervention was noticed in comparison with the RFA group (four of 14, 29%) ( p  < 0.01). Between the first and fifth procedure, post‐interventional adverse events tend to occur more frequently in patients with PDT (eight of 20, 40%) than with RFA (three of 14, 21%) ( p  = 0.277). Conclusions: Looking at the short‐term effects, we conclude that RFA may present a therapeutic alternative to PDT for palliative treatment of malignant biliary obstruction because of its simple feasibility and moderate adverse event rate. To provide a definitive evaluation of the long‐term effects and of overall median survival, a controlled trial with PDT must follow.